The economics of mobilization and inflation by Seymour E. Harris - Harris, Seymour Edwin (New York : Greenwood Press, 1968)
The major emphasis in this book is on the contribution of controls, the relation of direct and indirect controls, the technical problems of controls, the treatment of inflation, the problems raised y a rising national debt, the manner of supplementing price and related controls through subsidies, and the analysis and treatment of the economic "hang-over" following a war.
Bibliography: p. 288-291
osa; 06/08/18
Loans
Keywords: Economic policy; Inflation (Finance); Defenses; United States